International tourists in a ‘pacified’ favela: profiles and attitudes. The case of Santa Marta, Rio de Janeiro - Freire-Medeiros, Bianca; Vilarouca, Márcio Grijó; Menezes, Palloma (DIE ERDE – Journal of the Geographical Society of Berlin, 2013)
This article examines the experience of foreign tourists who have visited the Santa Marta favela in Rio de Janeiro after the recent “occupation” and “peacemaking” policy implemented by the Rio de Janeiro state government. The contribution is based on empirical research conducted with 400 international tourists who visited the community between March and May 2011. The study investigated the tourists’ profiles as well as their expectations and impressions of the visit. The article concludes with some reflections on how tourists evaluate not only the tourist facilities in the locality, but also their own experience as participants of the reality tour.